Effect of Saline Water Irrigation on the Yield and Mineral Composition of Crops in Rice-Wheat Cropping System - and S.S. Yadav, Ajay Kumar Yadav, P.K. Yadav Vinod Phogat, Abha Tikkoo (Journal of the Indian Society of Soil Science, 2015)
A screen house experiment was carried out in PVC columns to study the effect of saline water irrigation on yield and mineral composition of crops in a sandy loam soil in rice-wheat cropping system. Irrigation with different salinity levels (ECiw of 0.4, 2, 4, 6, 8 and 10 dS m-1) led to significant reduction in grain and straw yield of rice and wheat crops. A reduction of 55 and 15% in grain yields of rice and wheat was recorded as the ECiw increased from 0.4 to 2 dS m-1, which was more severe at 8 and 10 dS m-1 ECiw. Progressive increase in N, Na, Mg and Cl and decrease in P, K, Ca and SO4-S in rice grain and straw with increasing salinity of water was observed. A remarkable increase of 67, 357 and 113 per cent in N, Na and Fe content of rice grain was observed at 8 dS m-1 ECiw. A drastic reduction of 40, 36 and 25 per cent in P, SO4-S and Ca content of rice grain was recorded at 8 dS m-1 ECiw. Similarly in wheat, progressive increase in N, Na, Mg and Cl contents and decrease in P, K, Ca and SO4-S was observed with increasing salinity levels of irrigation water. A reduction of 21 and 24 per cent in P and K content of wheat grain and a sharp increase of 90 and 66 per cent in Na content of wheat grain and straw was obtained at 10 dS m-1. Wheat grain Cl content also showed a remarkable increase (66%) at ECiw of 10 dS m-1 as compared to ECiw of 0.4 dS m-1. The Fe, Zn, Mn and Cu contents in rice grain and straw increased with increasing salinity of water while in wheat straw and grain, Zn content increased with salinity of irrigation water. The Mn content of wheat straw and grain increased up to 6 dS m-1 ECiw but decreased at 8 and10 dS m-1 ECiw. The saline water irrigation increased soil ECe which was highest in the 10 dS m-1.